Current research in head and neck cancer: molecular pathways, novel therapeutic targets, and prognostic factors ; new insights into basic and translational research - Bier, Henning (Advances in oto-rhino-laryngology, 2005)
The development of head and neck cancer is a multistep process in which genetic as well as epigenetic alterations interfere with the regular functions of proto-oncogenes and tumor suppressor genes. In addition, carcinogenesis is promoted by the impairment of mechanisms responsible for the maintenance of genetic stability. The accumulation of crucial events such as evasion of apoptosis, lack of senescence, deregulated proliferation, invasion and metastasis, as well as neoangiogenesis eventually determines the malignant phenotype. The 16 articles of this volume span from advances in the understanding of underlying molecular pathways (conditional mouse model, folate activity, DNA repair, genomic heterogeneity, p53 family members, human papillomavirus), to preclinical and clinical studies investigating potential novel therapeutic targets (epidermal growth factor receptor, nuclear factor-kappaB, vascular endothelial growth factor, chemokine receptors, P53-based immunotherapy, virus-modified tumor vaccination), and biometric considerations on the evaluation of prognostic factors.This state-of-the-art publication is recommended reading not only for ENT specialists and oncologists, but also for molecular biologists and other subspecialists interested in head and neck cancer research